The phase separation effects in a pseudospin-electron model - Danyliv, O.D.; Stasyuk, I.V. (Condensed Matter Physics, 2002)
The two-sublattice pseudospin-electron model of high temperature superconductors
is studied with respect to phase separations. Such a model can
be used for the description of dielectric properties of YBaCuO-type crystals
along c -axis (the pseudospins represent an anharmonic motions of
apical oxygen O4). The model is treated within different approximations. It
is shown that the model has got phase transitions to the phase with pseudospin
ordering as well as phase separation. The effect of separation on
the appearance of the ordered state is discussed. Розглянуто двопідґраткову псевдоспін-електронну модель високотемпературних надпровідників з огляду на можливість появи фазових розшарувань. Така модель здатна описати діелектричні властивості кристалів типу YBaCuO вздовж осі c (псевдоспінами представлено ангармонічні локальні коливання вершинного кисню 04). Модель досліджено в різних наближеннях. Показано, що поряд з фазовим переходом у фазу із впорядкованою псевдоспіновою системою в моделі присутнє фазове розшарування. Обговорюється вплив розшарування на появу впорядкованої фази.